Philosophical aspects of Rehabilitation - Tittanegro, Gláucia Rita (O Mundo da Saúde, 2006)
Rehabilitation is a new possibility science has to reintegrate individuals in the community. To the expression “rehabilitation” are linked opposites like inclusion/exclusion, normal/abnormal, productive/not-productive. Productivity would imply power and its re- sult would be the product. That is what we can perceive from the Marxist philosophy. Product here he would be synonymous to action and people distanced from the production forces because of any anomaly would therefore be, excluded from the community, alienated, why not say, from their condition of human beings. We aim in this study to rethink Product as a passivity that means giving our own Self, a meaning more near the origin of the expression “Liturgy”. Rehabilitation is, according to this proposal, a Witnessing of Oneself: to answer for oneself and by oneself in Life’s Court means to answer to the Other for the Other, give back ability to the one who is different from us, respecting their difference. Respect and responsibility depend on the recognition of differences.